Assessment of Endoscopic Ultrasound for Predicting Preoperative T Staging in Patients With Gastric Adenocarcinoma - Wang, Yu‐Chih; Liao, Yi‐Jun; Lin, Wan‐Tzu; Liao, Szu‐Chia; Chen, Yi‐Ju; Wu, Cheng‐Chung; Wu, Feng‐Hsu (Journal of surgical oncology, 2025)
ABSTRACT Background and Objectives Endoscopic ultrasound (EUS) is an imaging modality that can be applied to predict preoperative T staging. It is important for the patient to decide whether to receive endoscopic therapy, surgical intervention, or neoadjuvant therapy. The objectives of our study were to (1) identify if EUS could precisely predict T1‐stage tumor, which is suitable for endoscopic treatment and (2) identify if EUS could precisely predict tumors more advanced than T3, which would mandate neoadjuvant therapy. Methods A retrospective study of patients who received gastrectomy was conducted from March 2017 to December 2021 at Taichung Veterans General Hospital. Those who received preoperative EUS, with final pathology showing gastric adenocarcinoma were included. Consistency of EUS prediction and pathology, accuracy, and parameters impacting accuracy were analyzed. Results The κ value was 0.6 if the T stage was not grouped, indicating moderate agreement. Overall accuracy was 52.8%. Overestimation and underestimation rates were 17.6% and 29.5%, respectively. The accuracy of T stages is highest in T1 (85.23%). The κ value of T1‐stage was 0.67, and those of T2, T3, and T4 were below 0.5. Regarding parameters affecting accuracy, we found longitudinal portion, Borrmann type, ulcer presentation, early gastric cancer, and size of tumor could influence the accuracy. Conclusions Our study showed that EUS was a good tool for precisely predicting T1‐stage of gastric adenocarcinoma preoperatively. For this situation, endoscopic treatment would be enough. However, for predicting more advanced gastric adenocarcinoma, EUS should be combined with other modalities to achieve better accuracy.